An exploratory study of participants' fit perceptions of customized garments. (25th August 2021) - Guo, Siming; Istook, Cynthia L.
Abstract : Purpose: The purpose of this study was to explore participants' fit perceptions of customized garments and investigate the factors that affected the customized fit. Design/methodology/approach: Because different patternmaking methods generate varied fit results, eight customized dresses were developed for four fit models aged 18–25 using two different made-to-measure (MTM) systems (Gerber AccuMark and Telestia Creator). The authors designed a questionnaire to assess the fit of the final garments on each of the four models. A total of 12 participants (four fit models and eight experts) attended a live evaluation meeting and completed the questionnaire. The quantitative and qualitative data of the participants' fit perceptions were collected and analyzed. Findings: The authors compared the fit outputs of the two MTM systems and determined the fit issues from the participants' perceptions. The results showed that the participants evaluated the customized fit mainly according to the ease, seam placement and wrinkle occurrence. The majority of fit models and experts preferred Dress B created using Telestia Creator to Dress A developed using Gerber AccuMark. The participants' fit perceptions also revealed that many factors, such as the MTM systems, participants' fit preferences, models' body characteristics, fabric and ease, impacted the fit results. In addition, the experts perceived more fit issues than the models. Originality/value: The fit output comparison of the two MTM systems could be valuable for pattern makers to use the systems. The research results would also be useful for apparel companies to conduct a fit evaluation and improve their customization processes.